Effects of sintering temperature on microstructural and dielectric properties of nickel-zinc ferrite prepared via sol-gel method - Jaiah @ Jais, Izzatil Ameerah (2016)
In this work, Ni0.5Zn0.5Fe2O4 were synthesized via sol-gel method. The effect of sintering temperature on the microstructure and dielectric properties of Ni0.5Zn0.5Fe2O4 were investigated. The ferrite samples were analyzed using X-Ray diffraction (XRD) to check the phases of the samples and to identify the formation of single phase Ni0.5Zn0.5Fe2O4. Field Emission Scanning Electron Microscope (FESEM) was used to get the magnified images of the morphology and microstructure of samples. The complex dielectrics of the samples were determined by HP 4192A LF Impedance Analyzer with setting of frequency range at 40 Hz up to 1 MHz while the measuring temperatures were fixed at 30°C and increased to 250°C. Keithley 236 Source which is connected to computer were set up for determining the DC conductivity of Ni0.5Zn0.5Fe2O4. Its measuring temperatures were fixed from 30°C to 250°C and the investigation involved the various sintering temperatures, starting at 600°C to 1100°C with increment of 50°C. The outcomes from XRD indicated that the single phase crystallization of Ni0.5Zn0.5Fe2O4 started to form at initial sintering temperature of 600°C and they exhibited as a single phase cubic spinel structure with lattice parameter 8.60 Å. The higher of sintering temperature give an optimum crystallization, with greater density and lesser porosity of Ni0.5Zn0.5Fe2O4, hence contributing to produce more compacted sample with superior properties. The FESEM micrographs showed that the average grain size of Ni0.5Zn0.5Fe2O4 nanoparticles was in the range of 59 nm to 199 nm with increasing sintering temperature from 600°C to 1100°C. This indicated that there was a grain growth occurred as the sintering temperature increased. Graphs of the frequency and sintering temperature dependence were tabulated for analyzing the variation of the dielectric constant and dielectric loss factor. The graphs trend show the dielectric constant and dielectric loss factor declined with greater frequency which is a standard dielectric properties of spinel ferrites. The Cole-Cole plots were tabulated to study the dielectric behavior of each sample. There are two primary relaxation mechanisms generated while sintering every pellet sample, hence indicating a non-debye relaxation type. The DC conductivity of Ni0.5Zn0.5Fe2O4 was analyzed to determine the conduction mechanism in the temperature reliance. As increasing sintering temperature, the values of electrical conductivity σdc increased representing the semiconducting behavior of the sample due to the upsurge the capability of the charge carriers to mobilize from grain-to-grain region in the samples.